A hybrid simulation approach to planning in a VMI supply chain. (6th March 2007) - Venkateswaran, Jayendran; Son, Young-Jun; Jones, Albert T.; Min, Hyeung-Sik J.
In this paper, we propose an innovative approach of integrating the vendor managed inventory (VMI) strategy with a hierarchical approach to production planning (HPP) decisions within a supply chain environment. The proposed architecture is divided into three stages: plan optimisation (Stages I), schedule optimisation (Stage II) and decision evaluation (Stage III). To implement this architecture, we use system dynamics simulations, discrete-event simulations and the High Level Architecture (HLA) as a distributed infrastructure. We describe our approach for the analysis of supply chains in detail and discuss results from experiments that demonstrate the benefits of the proposed architecture.